A pilot study to examine association of BMI with functional class and 6 min walk distance in idiopathic and heritable PAH: Possible association with estrogen metabolism. (25th September 2022) - MacLean, Margaret R.; Pandya, Divya; Swietlik, Emilia M.; Denver, Nina; Mair, Kirsty; Morrell, Nicholas W.; Gräf, Stefan; ,
Abstract: The hypothesis that a relationship exists between body mass index (BMI), functional class, and 6 min walk distance (6MWD) in Group 1‐pulmonary arterial hypertension (PAH) was examined. Analysis of data from the UK National Cohort Study for heritable pulmonary arterial/idiopathic PAH suggests increased BMI is a predictor of worse functional class and shorter 6MWD; increased body‐weight in mice and man may be associated with increased estrogen metabolism.